2013
DOI: 10.1002/ajpa.22341
|View full text |Cite
|
Sign up to set email alerts
|

Brief communication: Body mass index, body adiposity index, and percent body fat in asians

Abstract: Human obesity is a growing epidemic throughout the world. Body mass index (BMI) is commonly used as a good indicator of obesity. Body adiposity index (BAI = hip circumference (cm)/stature (m)(1.5) - 18), as a new surrogate measure, has been proposed recently as an alternative to BMI. This study, for the first time, compares BMI and BAI for predicting percent body fat (PBF; estimated from skinfolds) in a sample of 302 Buryat adults (148 men and 154 women) living in China. The BMI and BAI were strongly correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 46 publications
4
21
0
2
Order By: Relevance
“…However, only one study has attempted to validate the BAI on an Asian population. The results suggested that BMI was a more reliable indicator of BF% derived from skinfold thickness in adult Asian 21. Ethnic differences in hip circumference and height could exist, and the frequency of physical activity can also affect the measured value.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…However, only one study has attempted to validate the BAI on an Asian population. The results suggested that BMI was a more reliable indicator of BF% derived from skinfold thickness in adult Asian 21. Ethnic differences in hip circumference and height could exist, and the frequency of physical activity can also affect the measured value.…”
Section: Discussionmentioning
confidence: 92%
“…Our results were comparable to other recent studies which showed that BMI is more strongly associated with adiposity and metabolic risk factors than is BAI 16,17,18,19,20. BMI was more accurate surrogate for adiposity in American,19,20 Mexican Americans,17 Caucasian,18 and Asian subjects 21. Also one found that BMI was more strongly correlated with insulin sensitivity and type 2 diabetes risk 14.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations